Pengaruh Sistem Informasi Administrasi Kependudukan (SIAK) Terhadap Efektivitas Kerja Pegawai Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bogor - Dasmansyah Adyas; Lensie D Anggeraiyantie (JRB-Jurnal Riset Bisnis, 2018)
This study aims to determine: the influence of independent variables is Information Systems Administration Population (SIAK) which consists of (according to procedures, have special standards, and orderly administration) partially and simultaneously to the dependent variable of Employee Effectiveness on the Department of Population and Civil Registry Bogor. Population in this research is employee who use application of information system of administration of population (SIAK), with sample of 45 employee by using Sampling Saturation technique that is sample determination technique when all member of population used as sample. The method of analysis using multiple regression analysis. From the research results obtained regression equation, shows a positive value. The hypothesis test result for partial test (t test) shows that when independent variables independently there is no influence on the dependent variable. While the three independent variables have an influence on the dependent variable. From result of determination coefficient test of Adjusted R Square value obtained by 0,320 (32%), while the rest 68% influenced by other factor not examined in this research.